Aggregation of Recombinant Monoclonal Antibodies and Its Role in Potential Immunogenicity - Ignjatovic, Janko; Svajger, Urban; Ravnikar, Matjaz; Molek, Peter; Zadravec, Darko; Paris, Alenka; Strukelj, Borut (Current Pharmaceutical Biotechnology, 2018)
Background: Development of new recombinant biotechnology products has greatly expanded in the field of modern pharmacy and medicine. Since biological recombinant molecules are sensitive, simple or composed proteins, their function is heavily dependent on their structure. In addition to their efficacy, biological medicinal products could show side effects such as immunogenicity. Therefore, detection and characterization of protein structural variants is essential during development and quality control of therapeutic proteins that might trigger immunogenic response in organism. Methods: This article includes proposed detection and characterization of aggregated, as well as other modified forms of monoclonal antibodies (mAb), by using selected chromatographic and spectrometric methods. Additionally, selected mAb's aggregates and modified structural variants of monoclonal antibodies were subjected to the immature monocyte-derived dendritic cells' (DC) examination experiment for monitoring of activated DC cells in order to determine potential immunogenicity of mAb structural variants. Furthermore, potential innate immunogenic response of peripheral blood mononuclear cells (PBMC) cultures to mAb aggregates was also evaluated by measuring pro-inflammatory cytokine response during early exposure of PBMCs to different mAb samples and by determining the effect of mAb aggregates on PBMC proliferation during long-term cultures. Result and Conclusion: All developed and proposed analytical methods and immunological in vitro DC and PBMC assays, could be used as platform for complementary analytical characterization and determination of potential for immunogenicity for all biopharmaceutical products which contain monoclonal antibodies as active pharmaceutical ingredients.
Keywords: immunogenicity